Design and synthesis of BRC analogous peptides and their interactions with a key p53 peptide. Issue 20 (3rd October 2018) - Zhao, Dongxin; Lu, Kui; Liu, Guangbin; Ma, Li; Zhu, Hanjing; He, Juan
Abstract : Mutations in breast cancer susceptibility gene 2 ( BRCA2 ) can lead to chromosomal instability and result in breast cancer, which is strongly associated with p53 mutations. Here, based on the crystal structure of BRC4 and p53, the spatial structure of BRC2 and p53 (171–192) was simulated, providing structural basis for the site‐specific mutation of BRC2. The BRC analogous peptides and p53 (171–192) were synthesized, and the interaction between the mutant peptide and p53 (171–192) was studied using circular diachronic spectroscopy and fluorescence spectroscopy. The results show that the mutations of amino acid residues constituting the BRC2 α‐helix significantly affect the structure and interaction of BRC analogs and p53 (171–192), which provides support for understanding the structure of the BRC repeat motifs and its interaction pattern with p53. Abstract :